As escolas polivalentes do Triângulo Mineiro e Alto Paranaíba (MG): sondagem vocacional no projeto desenvolvimentista civil-militar (1965–1976) - Resende, Luciana Araujo Valle de (2015)
This study has as object eight state vocational schools located in Araguari, Araxá, Frutal, Ituiutaba, Monte Carmelo, Patos de Minas, Uberaba and Uberlândia, in Minas Gerais. The period analyzed comprises the years from 1965 to 1976, from the signature of the Agreement 512-11-610-042 beteween the Ministry of Education and Culture (MEC) and the American Agency for International Development (USAID), which started a series of other agreements, and actions ending up with the creation of the Expansion and Improvement of High Schools Program (Programa de Expansão e Melhoria do Ensino Médio - PREMEM) and, from this, the Vocational Schools. The upper limit of the study, 1976, was the year when these agreements, known as MEC/USAID agreements ceased. The Vocational Schools were characterized as vocation probing schools, directing the professional formation of the population in general, which would happen a posteriori, turning it shorter and more effective, since the labor market would demand, urgently, capable professionals for an expanding economy. The project of Vocational Schools had a national scope, and foresaw, for its unfolding, the complete substitution of State Schools for the new model, called “multi-curricula”. The theme Vocational schools was the object of my Master’s degree study, when I focused the State School Guiomar de Freitas Costa, in Uberlândia. That study raised questionings and concerns that resulted in the central problem of the thesis presented here: understanding the measure in which such schools integrated the country’s development project – mostly in the first half of the military rule – and to understand its structure, functionality and efficacyThe development of the study presented here, demanded the use of several sources: 1) specialized literature about the topics presented, i.e., the situation of national education in a temporal analysis, the political, economical and social context, research methodologies, the theory of human capital, vocational teaching, pedagogical trends and practices, agreements MEC-USAID and PREMEM; 2) national, state and county laws related to the discussion: laws of national education directives and basis, decrees and reports stating about the program of technical cooperation between Brazil and the United States of America, the Program of Expansion and Improvement of Teaching (PREMEM), formation of professors, establishment of Vocational Schools and educational planning; 3) documentation of school archives: books of minutes of Collegiate and of faculty and staff, registrar books with final scores, enrolment, visits of inspector, accounting books, punch clock records, student, professor and staff occurrences, inventory, class schedules, school year calendar, school rules, class reports, payment rolls, bills of sales, exchanged mail, personal documentation of professional personnel, documents of land acquisition, blueprints, manuals of PREMEM, didactic materials/resources used in classes, books available in the school library, structured evaluations for follow-up of school processes, pictures of events, texts prepared for special dates, and news from the official newspaper and, finally, 4) national and local press reports, especially from Folha de São Paulo, Correio de Araxá, Correio de Uberlândia and Lavoura e Comércio (Uberaba). The proposition of Vocational schools was conciliate theoretical and practical formation through an active education permeated by technological resources. The contact with knowledge and several practical activities under professional supervision, the student would identify the knowledge area that would interest him the most and his aptitude. This formation in primary school would make way for the vocation studies in high school, which became mandatory by the law 5.692/71, that reformed school education from the previous levels of elementary, middle high and high school. However, the multi-curricula proposal that would be spread to the other public schools in the country ended up succumbing to the model already established. From its ephemeral existence, maybe the Vocational Schools have not reached the more general goals in political, economic and social aspects; however, this study demonstrated that, for the people that, directly or indirectly, had contact with such schools, a legacy of vocational and quality teaching was made, so much so, that forty years after the end of that proposal, they are still remembered.